2019
DOI: 10.18514/mmn.2019.2424
|View full text |Cite
|
Sign up to set email alerts
|

On the Volterra Delay-Integro-Differential equation with layer behavior and its numerical solution

Abstract: In this paper, we analyze the convergence of the fitted mesh method applied to singularly perturbed Volterra delay-integro-differential equation. Our mesh comprises a special nonuniform mesh on the first subinterval and uniform mesh on another part. Error estimates are obtained using difference analogue of Gronwall's inequality with delay. A numerical test that confirms the theoretical results is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The construction of the difference scheme is a combination of hybrid difference scheme on a Shishkin-type mesh and appropriate quadrature rules. Error estimates are obtained by using the truncation error estimate techniques and a discrete analogue of Grönwall's inequality and it is shown that the scheme is O(N −2 ln 2 N) order convergent, which improves the numerical results given in [7,[12][13][14]. Numerical experiments are presented to support the theoretical result.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The construction of the difference scheme is a combination of hybrid difference scheme on a Shishkin-type mesh and appropriate quadrature rules. Error estimates are obtained by using the truncation error estimate techniques and a discrete analogue of Grönwall's inequality and it is shown that the scheme is O(N −2 ln 2 N) order convergent, which improves the numerical results given in [7,[12][13][14]. Numerical experiments are presented to support the theoretical result.…”
Section: Introductionmentioning
confidence: 72%
“…Kudu et al [7] proposed an implicit finite difference method on a piecewise uniform Shishkin-type mesh with appropriate quadrature rules for a singularly perturbed delay integro-differential equation and showed that the scheme is almost first-order convergent. Amiraliyev and Yapman [12] used a fitted mesh method to solve a singularly perturbed Volterra delay-integro-differential equation and indicated that the scheme is also almost first-order convergent. Yapman et al [13] developed a numerical method of integral identities with the use of exponential basis functions and interpolating quadrature rules for a singularly perturbed nonlinear Volterra integro-differential equation with delay and proved that the scheme is first-order uniform convergent.…”
Section: Introductionmentioning
confidence: 99%
“…Proof. The proof is done by similar approach as in [5,12]. Now, we turn to establishment of the difference scheme.…”
Section: The Mesh and Difference Schemementioning
confidence: 99%
“…On account of 2) , it is found that [3,6,19,29,33]. b) Now, we consider the node points of Bakhvalov type mesh.…”
Section: Now We Consider the Casementioning
confidence: 99%
“…Some existence and uniqueness results about singularly perturbed problems have been given in [15,23]. In recent times, notable techniques and various numerical schemes have been presented for singularly perturbed integro-differential equations (see [2,6,9,10,13,17,19,25,29,[33][34][35]). Our aim in this paper is to present a uniform numerical method for solving singularly perturbed nonlinear integro-differential equations and compare the obtained results on Bakhvalov and Shishkin type meshes.…”
Section: Introductionmentioning
confidence: 99%